Increased Plasma Levels of Tissue Factor Pathway Inhibitor (TFPI) after n-3 Polyunsaturated Fatty Acids Supplementation in Patients with Chronic Atherosclerotic Disease - Berrettini, Mauro; Parise, Pasquale; Ricotta, Serena; Iorio, Alfonso; Peirone, Cristina; Nenci, Giuseppe G (Thrombosis and Haemostasis, 1996)
This double-blind, randomised, controlled study examined the effect of a daily dosage of 3 g n-3 polyunsaturated fatty acids (n-3 PUFA) on plasma lipids and some haemostatic factors in 40 patients with chronic atherosclerotic diseases. Serum lipids, factor VII, tissue factor pathway inhibitor (TFPI) and prothrombin activation fragment 1+2 (F1+2) were measured at baseline and after 2, 8, and 16-week supplementation of either n-3 PUFA or com oil. Administration of n-3 PUFA promptly lowered serum triglycerides and increased LDL-cholesterol (-32% and +33%, respectively, after 2 weeks of treatment) while a significant increase (+31%) in HDL-cholesterol was documented at the end of the observation period. Treatment with n-3 PUFA induced a progressive significant increase of TFPI plasma levels (+21% after 16 weeks; p = 0.029). TFPI activity was significantly correlated with LDL-cholesterol, and multiple stepwise regression analysis showed that LDL-cholesterol was the most important predictor of TFPI activity. Plasma levels of the inhibitor showed also a very high parallelism in their trend over time (ANOVA model for homogeneity of slopes) with both HDL-cholesterol (p = 0.82) and LDL-cholesterol (p = 0.67). Patients treated with n-PUFA also showed a significant reduction of F1+2 plasma levels (p = 0.016) while no significant changes were detected in plasma factor VII clotting activity. Lipid and haemostatic parameters were not modified at any study time in patients receiving corn oil as placebo. The results of this study confirm the effects of n-3 PUFA administration on plasma lipids and show that in patients with chronic atherosclerotic disease a 16-week supplementation with these compounds induces a small but statistically significant increase of TFPI plasma levels with a parallel down-regulation of the extrinsic pathway of blood coagulation which may be relevant to the antithrombotic activity of fish diet and fish oil derivatives.